ANALYTICAL METHOD DEVELOPMENT AND VALIDATION OF ATOMOXETINE HYDROCHLORIDE USING RAPID HIGH-PERFORMANCE LIQUID CHROMATOGRAPHIC TECHNIQUE - Rahman, Zubaidur; Aanandhi M, Vijey; M, Sumithra (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: A simple, novel, sensitive, rapid high-performance liquid chromatographic (RP-HPLC) method has been developed and validated for quantitative determination of atomoxetine HCl (ATH) in bulk and formulations. Methods: The chromatographic development was carried out on RP-HPLC. The column used as Xterra RP 18 (250 mm Ã— 4.6 mm, 5 Î¼ particle size), with mobile phase consisting of methanol: water 80:20 V/V. The flow rate was 1.0 mL/min and the effluents were monitored at 270 nm. Results: The retention time was found to be 5.350 min. The method was validated as per International Conference on Harmonization Guideline with respect to linearity, accuracy, precision, and robustness. The calibration curve was found to be linear over a range of 2â€“10 Î¼g/mL with a regression coefficient of 0.9999. The method has proved high sensitivity and specificity. Conclusion: The results of the study showed that the proposed RP-HPLC method was simple, rapid, precise and accurate which is useful for the routine determination of ATH in bulk drug and in its pharmaceutical dosage form.